ANALISIS ASPEK BIOFISIK DALAM PENILAIAN KERAWANAN BANJIR DI SUB DAS SAMIN PROVINSI JAWA TENGAH - Wiwin Budiarti; Evi Gravitiani; Mujiyo Mujiyo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Floods a main problem in Samin sub watershed, which is part of the Bengawan Solo watershed, Central Java Province. Assessment of the flood vulnerability level and its determinant causes is required as a basis information for policy makers to design a flood mitigation strategy. This study aims to assess the level of flood vulnerability and to analyze the biophysical aspects that caused flooding in Samin sub watershed. The method used is survey and the quantitative analysis of biophysical aspects including slope, soil, drainage density, land use and rainfall using map-overlay and scoring approach. Data analysis using Geographic Information System (GIS) technology. The results showed that the Samin sub-watershed areas has five levels of flood vulnerability is the category of "not vulnerable" area of 2188.44 ha (3.45%), "rather vulnerable" area of 3194.17 ha (5.03%), "quite vulnerable" area of 5379.17 ha (8.47%), "vulnerable" area of 31006.51 ha (48.83%) and "very vulnerable" area of 21726.56 ha (34.22%). The level is vulnerable - very vulnerable mostly spread in the middle and downstream Samin sub-basins including the District Polokarto, Sukoharjo, Mojolaban, Bendosari, Jumantono, Karanganyar, Kebakkramat, Jaten. While the level is rather vulnerable - not prone areas spread in the upstream sub-basins that is District Tawangmangu, Jatiyoso, Ngargoyoso. Correlation analysis results show that the most dominant biophysical aspects that caused flooding in Samin sub watershed is the slope, drainage density and land use.